Collective impact capacity building: Finding gold in Southwest Florida. Issue 2 (14th March 2016) - Banyai, Cindy; Fleming, Dave
Abstract: The Southwest Florida Community Foundation is leading an emergent process of collective impact and capacity building. The Foundation's regional initiative and collective impact work, including the FutureMakers Coalition, is explored here as a community development strategy. Building collective impact capacity to support the Foundation's regional initiatives includes organizing grantees into "tribes" to develop collaborative networks and facilitate concentrated organizational and leadership capacity building, and levering its grant processes to build collective impact and program capacity. The Foundation team relies on the Tribal Alchemy framework and the Getting to Outcomes model to enhance understanding and execution of collective impact and increase capacity of organizations in the region. The development of the systems of the FutureMakers Coalition in support of collective impact is also explored. This work contributes to theory use in collective impact capacity building and discusses real-world ongoing processes.